Meiofauna increases bacterial denitrification in marine sediments - Bonaglia, S.; Nascimento, F. J. A; Bartoli, M.; Klawonn, I.; Brüchert, V. (Nature communications, 2014)
Denitrification is a critical process that can alleviate the effects of excessive nitrogen availability in aquatic ecosystems subject to eutrophication. An important part of denitrification occurs in benthic systems where bioturbation by meiofauna (invertebrates <1 mm) and its effect on element cycling are still not well understood. Here we study the quantitative impact of meiofauna populations of different abundance and diversity, in the presence and absence of macrofauna, on nitrate reduction, carbon mineralization and methane fluxes. In sediments with abundant and diverse meiofauna, denitrification is double that in sediments with low meiofauna, suggesting that meiofauna bioturbation has a stimulating effect on nitrifying and denitrifying bacteria. However, high meiofauna densities in the presence of bivalves do not stimulate denitrification, while dissimilatory nitrate reduction to ammonium rate and methane efflux are significantly enhanced. We demonstrate that the ecological interactions between meio-, macrofauna and bacteria are important in regulating nitrogen cycling in soft-sediment ecosystems. Excessive nutrient loading is a threat to aquatic ecosystems; however, denitrification may be key in removing large amounts of reactive nitrogen and, therefore, mitigating consequent eutrophication. Here, the authors explore how meiofauna may impact the rate of denitrification in sediments.